2013
DOI: 10.1186/bcr3419
|View full text |Cite
|
Sign up to set email alerts
|

Parity induces differentiation and reduces Wnt/Notch signaling ratio and proliferation potential of basal stem/progenitor cells isolated from mouse mammary epithelium

Abstract: IntroductionEarly pregnancy has a strong protective effect against breast cancer in humans and rodents, but the underlying mechanism is unknown. Because breast cancers are thought to arise from specific cell subpopulations of mammary epithelia, we studied the effect of parity on the transcriptome and the differentiation/proliferation potential of specific luminal and basal mammary cells in mice.MethodsMammary epithelial cell subpopulations (luminal Sca1-, luminal Sca1+, basal stem/progenitor, and basal myoepit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 55 publications
10
78
0
Order By: Relevance
“…Thus, whereas many laboratories are now routinely producing high-throughput data sets, and methodologies for analyzing such data have been described in the literature, the vast majority of groups that produce data have to develop collaborations with expert computational groups to apply these methods. Indeed, in recent years MARA has been applied to a large range of mammalian systems studied by various experimental collaborators and experimentally validated predicted regulatory circuitry in these systems (Summers et al 2010;Aceto et al 2012;Arner et al 2012;Hasegawa et al 2012;Pérez-Schindler et al 2012;Suzuki et al 2012;Eisele et al 2013;Meier-Abt et al 2013;Tiwari et al 2013a,b;Vervoort et al 2013). Although these studies further validated the power of the method, they required a considerable investment of time and effort for the analysis of each new data set.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Thus, whereas many laboratories are now routinely producing high-throughput data sets, and methodologies for analyzing such data have been described in the literature, the vast majority of groups that produce data have to develop collaborations with expert computational groups to apply these methods. Indeed, in recent years MARA has been applied to a large range of mammalian systems studied by various experimental collaborators and experimentally validated predicted regulatory circuitry in these systems (Summers et al 2010;Aceto et al 2012;Arner et al 2012;Hasegawa et al 2012;Pérez-Schindler et al 2012;Suzuki et al 2012;Eisele et al 2013;Meier-Abt et al 2013;Tiwari et al 2013a,b;Vervoort et al 2013). Although these studies further validated the power of the method, they required a considerable investment of time and effort for the analysis of each new data set.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Altogether, these studies point to HS-MECs exerting a powerful developmental influence on the normal MEC population. Accumulating evidence indicates that HS-MECs also influence breast cancer susceptibility (Choudhury et al 2013, Hodgson et al 2013, Meier-Abt et al 2013, Tarulli et al 2013, an effect that may extend to both ERa-positive and ERa-negative breast cancers, and supports the use of androgen modulation as a form of breast cancer therapy as it principally targets the HS-MEC population.…”
Section: The Mammary Epithelium Is a Developmentally Dependent Organmentioning
confidence: 99%
“…In recent studies, it was reported that Notch and Wnt signaling is the main cell fate regulator in breast cancer (3,4), making them potential therapeutic targets in BCSCs. miRNAs are a conserved class of noncoding small RNAs that regulate the expression of certain key genes involved in selfrenewal, survival, and tumor progression (5).…”
Section: Cd24mentioning
confidence: 99%
“…Primary cells from nude mice were infected with control or miR34a lentivirus (GenTarget Inc.; multiplicity of infection, [3][4][5] in the presence of 5 mg/mL polybrene. Mice were anesthetized with 150 mL of saline/Zoletil/Rompun (7:1:1) and inoculated subcutaneously with 1 Â 10 6 stable MCF7/ADR primary cells into each flank.…”
Section: Lentiviral-mediated Mirna Overexpression and Xenograftmentioning
confidence: 99%